2009
DOI: 10.1159/000235579
|View full text |Cite
|
Sign up to set email alerts
|

Major Cerebral Events in <i>Staphylococcus Aureus</i> Infective Endocarditis: Is Anticoagulant Therapy Safe?

Abstract: Objectives: To study the impact of anticoagulation on major cerebral events in patients with left-sided Staphylococcus aureus infective endocarditis (IE). Methods: A prospective cohort study; the use of anticoagulation and the relation to major cerebral events was evaluated separately at onset of admission and during hospitalization. Results: Overall, 70 out of 175 patients (40%; 95% CI: 33–47%) experienced major cerebral events during the course of the disease, cerebral ischaemic stroke occured in 59 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Fewer CVC among warfarin treated patients was seen for all microbiological aetiologies, but the difference was significant for episodes caused by Staphylococcus aureus only, as separately described [31]. This uniform pattern irrespective of NVE causative organism supports the results of the multivariate analysis with an independent association between warfarin use and lower CVC incidence.…”
Section: Discussionsupporting
confidence: 76%
“…Fewer CVC among warfarin treated patients was seen for all microbiological aetiologies, but the difference was significant for episodes caused by Staphylococcus aureus only, as separately described [31]. This uniform pattern irrespective of NVE causative organism supports the results of the multivariate analysis with an independent association between warfarin use and lower CVC incidence.…”
Section: Discussionsupporting
confidence: 76%
“…On the contrary, more recent studies have suggested a reduced risk of brain embolism without significant hemorrhagic complications in patients on anticoagulation [4, 5]. The authors of these studies argue that the risk of ICH related to anticoagulation has been overestimated and ACT is not associated with ICH, instead having a protective effect against embolic events in IE patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also reported that the incidence of cerebrovascular complications and mortality was increased when ACT was discontinued in patients with prosthetic valve IE [3]. Moreover, some recent studies have shown that warfarin use before IE diagnosis is associated with a reduced risk of cerebral events, suggesting the effectiveness of ACT in the prevention of embolization in IE patients [4, 5]. …”
Section: Introductionmentioning
confidence: 96%
“…Thrombosis in the femoral vein would, however, be expected to be different due to the femoral vein's large size and large clot load. 6 While some argument for the safety of anticoagulation with endocarditis has been made in the general population, 7 there are no such data for ESRD patients. The combination of systemic anticoagulation with heparin and acute bacterial endocarditis was, indeed, the worst possible confluence of events for this patient and likely contributed to the catastrophic intracranial bleed.…”
Section: Discussionmentioning
confidence: 99%